Impact of News on Indian Stock Market: A Periodic Study with Asymmetric Conditional Volatility Models. (August 2016) - Amit,; Bammi, Ruchika
The article analyzes the leverage effect for Indian stock market. The effect of good and bad news on volatility during the period of growth, recession and the post-recession period is investigated taking American recession of 2008–2009 as the benchmark. Bombay Stock Exchange (BSE) 30 index was used as the proxy for Indian stock market. Using suitable asymmetric generalized autoregressive conditional heteroscedasticity (GARCH) models based on information criterions to study the asymmetry for the period and sub-periods, it was found that Indian stock market reacts differently to positive and negative news confirming leverage effect in all periods considered. However, the leverage effect was seen prominent during the period of gloom than other periods shown by the news impact curve.